Methane emission from stems of European beech (Fagus sylvatica) offsets as much as half of methane oxidation in soil - Machacova, Katerina; Warlo, Hannes; Svobodová, Kateřina; Agyei, Thomas; Uchytilová, Tereza; Horáček, Petr; Lang, Friederike (The New phytologist, 2023)
Trees are known to be atmospheric methane (CH4 ) emitters. Little is known about seasonal dynamics of tree CH4 fluxes and relationships to environmental conditions. That prevents the correct estimation of net annual tree and forest CH4 exchange. We aimed to explore the contribution of stem emissions to forest CH4 exchange. We determined seasonal CH4 fluxes of mature European beech (Fagus sylvatica) stems and adjacent soil in a typical temperate beech forest of the White Carpathians with high spatial heterogeneity in soil moisture. The beech stems were net annual CH4 sources, whereas the soil was a net CH4 sink. High CH4 emitters showed clear seasonality in their stem CH4 emissions that followed stem CO2 efflux. Elevated CH4 fluxes were detected during the vegetation season. Observed high spatial variability in stem CH4 emissions was neither explicably by soil CH4 exchange nor by CH4 concentrations, water content, or temperature studied in soil profiles near each measured tree. The stem CH4 emissions offset the soil CH4 uptake by up to 46.5% and on average by 13% on stand level. In Central Europe, widely grown beech contributes markedly to seasonal dynamics of ecosystem CH4 exchange. Its contribution should be included into forest greenhouse gas flux inventories.
Keywords: European beech; Trees; Forests; tree stem; Ecosystem; lesy; stromy; CH4 flux; uptake; Methane; půda; soil; temperate montane forest; Carbon Dioxide; seasonal dynamics; buk (rod); oxid uhličitý; emission; Soil; methan; Fagus; ekosystém